2010 4th International Conference on Bioinformatics and Biomedical Engineering 2010
DOI: 10.1109/icbbe.2010.5515547
|View full text |Cite
|
Sign up to set email alerts
|

Cd²+-Adsorption Properties in Wastewater of Composite Modified Maifan Stone

Abstract: A new kind of Cd 2+ adsorption material was prepared using maifan stone by composite modification with chemical and heat treatment methods. The modified maifan stones were characterized by SEM and EDS. Effects of the modified maifan stone content, contact time and the initial pH of the solution on the adsorption of Cd 2+ were studied. The research results show as follows: 1) The composite modified maifan stone was prepared with heat treatment for 1 h at 340 ℃ after the chemical dipping for 24 h with 2 mol/L Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…2 showed that when the content of Ni-Cu-coated glass fibers was less than 6 wt %, the coating resistivity decreased significantly as the amount of the fibers was added; when the fiber content reached 6 wt %, the resistance of the coating had a minimum value; and continue to increase the fiber content, the resistivity of coating increased. This is because the conductivity of the coatings mainly depends on the fillers and polymer binders together form the close-grained degree of the electrical conductivity of the network at this point [8]. So, the appropriate adding amount of Ni-Cu-coated glass fibers was 6 wt %, the composite coating resistivity had a minimum value of 1.13 cm ⋅ Ω .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 showed that when the content of Ni-Cu-coated glass fibers was less than 6 wt %, the coating resistivity decreased significantly as the amount of the fibers was added; when the fiber content reached 6 wt %, the resistance of the coating had a minimum value; and continue to increase the fiber content, the resistivity of coating increased. This is because the conductivity of the coatings mainly depends on the fillers and polymer binders together form the close-grained degree of the electrical conductivity of the network at this point [8]. So, the appropriate adding amount of Ni-Cu-coated glass fibers was 6 wt %, the composite coating resistivity had a minimum value of 1.13 cm ⋅ Ω .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 1 showed that the shielding effectiveness of the coatings containing 6 wt% Ni-Cu-coated glass fibers had dramatically increased. This was because the completeness and closely knit degree of the conductivity network in the coatings achieved the best when the mass fraction of Ni-Cu-coated glass fibers reaches a critical value [8]. The close electrical conductivity network of the shielding coatings significantly improved the attenuation degree of the incident electromagnetic wave energy to enhance the shielding effectiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation